My heart can't beat unless you tell it to [videorecording (DVD)] - Schram, Ingrid Sophie; Fugit, Patrick, 1982-; Campbell, Owen (Actor) (Dark Sky Films, 2021)
Dwight and his sister Jessie reach a crossroads over what to do about their younger brother Thomas' mysterious illness. The increasingly dangerous task of keeping him alive weighs heavy on sensitive Dwight, and as a fiercely private and close-knit family unit, Thomas and Jessie depend on him and the rituals they've learned in order to keep their secret. Dwight yearns for another life, but Jessie will stop at nothing to keep her family together.